Effect of Valsartan on Echo Cardio Graphic Fraction Shortening, Troponin I, Malondialdehyde in Trastuzumab Treated Females with Breast Cancer - Maysaa Ali Abdul Khaleq (Journal of Global Pharma Technology, 2017)
Background: Trastuzumab therapy is highly effective in HER2 positive breast cancer patients, but it is complicated by cardio toxicity. Objective: To elucidate the possible effects of valsartan medication on echocardiographic fraction shortening, serum troponin I and serum malondialdehyde in trastuzumab treated patients with HER2 positive breast cancer. Patients and Methods: A total of twenty six female patients with HER2 positive breast cancer were enrolled in this study. The patients were randomized into two groups, thirteen patients in each group. Group I included patients who received trastuzumab medication for 8 cycles with 21 days apart. Group II included patients who treated with trastuzumab medication with valsartan 40 mg, orally, once daily dose for 8 cycles. Echocardiography was used to measure fraction shortening at zero time, 4th and 8th cycles in both groups Serum troponin I and malondialdehyde were measured at zero time, 2nd, 4th, 6th and 8th cycles in both groups. Results: Treatment with trastuzumab medication caused a significant reduction in echocardiographic fraction shortening at an only 8th cycle in comparison to baseline level readings (P < 0.05). Combined trastuzumab plus valsartan medications caused a significant increment in echocardiographic fraction shortening in comparison with that of trastuzumab medication group (P < 0.05). Regarding serum troponin I and malondialdehyde, trastuzumab medication caused a significant increment in both these markers compared with those baseline readings (P < 0.05). Combined trastuzumab plus valsartan caused significant reduction in troponin I and malondialdehyde in comparison with that of trastuzumab medication group (P < 0.05). Conclusion: Valsartan causes significant increase in echocardiographic fraction shortening level and cause significant reduction in serum troponin I and malondialdehyde in trastuzumab treated patients.Keywords: Valsartan, Trastuzumab, Cardiotoxicity, Fraction shortening, Troponin I, MDA.